Air to Water Generator Integrated System Real Application: A Study Case in a Worker Village in United Arab Emirates - Lucia Cattani; Paolo Cattani; Anna Magrini (Applied Sciences, 2023)
The water crisis is currently affecting billions of people. To mitigate the issue, unconventional water sources should be taken into account. Among them, atmosphere is a promising possibility, but it is still considered a novel source, and more studies, based on real results concerning the behaviour of the Atmospheric/Air-to Water Generator (AWG) systems, also known as Atmospheric Water Harvesting (AWH) systems, are needed to prove the water extraction sustainability. The current research work describes the real application of an integrated AWG system, based on a thermodynamic reverse cycle, designed to extract water from air and take advantage of the other useful effects of the cycle at the same time. The integrated machine was placed in Dubai, in a worker village, and tested. The machine is able to provide, at the same time, with the same energy consumption, water, heating and cooling energy. On the basis of onsite measurements, calculations about the efficiencies, using the Water Energy Transformation (WET), plastic savings, due to bottled water avoidance, and economic sustainability were carried out. The work answers to research questions concerning the potentiality of integrated systems in Heating Ventilation Air Conditioning (HVAC) plants revamping, the economic sustainability of water extraction from air and the lack of tests on real AWG machines of thousand-litre production capability (large size).